2020
DOI: 10.3389/feduc.2020.00151
|View full text |Cite|
|
Sign up to set email alerts
|

An Exploration of the Metaphors and Images Used to Describe Leadership in Two Different Cultural Contexts

Abstract: This paper is developed from qualitative data exploring the metaphors used to describe women's leadership in differing cultural contexts. Metaphors are a useful communication tool, allowing us to understand an idea or concept through some other phenomenon. Understandably, studies of metaphor tend to focus on metaphors deriving from the English language and from Western cultures. Our everyday language literature abounds with metaphors that evoke images of the masculine-including of machines, war and fighting, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…This gender division may be linked to stereotypes and individual de nitions around what constitutes leadership. (33)(34)(35) Traditionally, leadership has been linked to masculine traits, which then also devalue the feminine style of leadership. (34,35) Johnson and Blair discuss how COVID-19 is shifting this understanding of leadership.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This gender division may be linked to stereotypes and individual de nitions around what constitutes leadership. (33)(34)(35) Traditionally, leadership has been linked to masculine traits, which then also devalue the feminine style of leadership. (34,35) Johnson and Blair discuss how COVID-19 is shifting this understanding of leadership.…”
Section: Discussionmentioning
confidence: 99%
“…(33)(34)(35) Traditionally, leadership has been linked to masculine traits, which then also devalue the feminine style of leadership. (34,35) Johnson and Blair discuss how COVID-19 is shifting this understanding of leadership. (34) This idea will be further explored in interviews with eld epidemiologists in another publication.…”
Section: Discussionmentioning
confidence: 99%
“…This line of inquiry has problematized several perspectives in conceptualizing educational leadership. Studies have revealed that commonly used metaphors in leadership heavily rely on gender-binaries and muscularity (Ashcraft and Muhr, 2018;MacDonald, 2019;Randell and Yerbury, 2020), middle-class and Anglo-centric norms (Wilkinson, 2008;MacDonald, 2019), as well as military-centered vocabularies (Ashcraft and Muhr, 2018;Armstrong et al, 2020). For example, pointing out the fact that military metaphors are commonly used for schools and educators, Armstrong et al (2020) explored the way school principals achieved social justice goals and strategies using war-normalizing metaphors.…”
Section: Metaphor As a Theoretical And Analytical Tool: Reflection Of...mentioning
confidence: 99%
“…In this self-reported survey, this raises questions on whether leadership has the same meaning or interpretation across genders. The difference in response between genders may be linked to stereotypes and individual definitions around what constitutes leadership [33][34][35]. Traditionally, leadership has been linked to masculine traits, which then also devalue the feminine style of leadership [34,35].…”
Section: Emergency Responsementioning
confidence: 99%
“…The difference in response between genders may be linked to stereotypes and individual definitions around what constitutes leadership [33][34][35]. Traditionally, leadership has been linked to masculine traits, which then also devalue the feminine style of leadership [34,35]. Johnson and Blair discuss how COVID-19 is shifting this understanding of leadership [34].…”
Section: Emergency Responsementioning
confidence: 99%